A Review of Large-Scale Kinetic Parameters in Metabolic Network Model of Escherichia coli - Azrag, M. A. K.; Tuty Asmawaty, Abdul Kadir; Mohd Arfian, Ismail (American Scientific Publisher, 2018)
Metabolic engineering is attentive about the alteration properties of metabolic pathways with the point of improving the generation of a few metabolics of intrigue. An essential range of metabolic engineering, the development is quite useful in the parameter identification/estimation of kinetic parameters in the metabolic pathway. The development of metabolic kinetic model requires a detailed information of the initial concentration of enzymes, metabolites, co-metabolites, kinetic parameters and the cell condition. However, kinetic parameters play a significant role in building dynamic model. Kinetic parameters identification is usually used to reduce the errors in the simulation of the model or in the estimation of the model’s enzymes and metabolites. Moreover, the inverse problem, irreversible problem and the large scale attributes are the main issues to be considered for optimizing and estimating large scale kinetic parameters. This paper highlights the challenges inherent in the identification/estimation of kinetic parameters and the methods applied in solving the problems in the kinetic metabolic model of E. Coli following comprehensive analyses and discussions.